Prevalence and correlates of depression and depression-anxiety in patients receiving gastroscopy - Hua, Fan; Chang, Liu; Chun, Li Xin (Frontiers in Psychiatry, 2025)
ObjectiveThere are increasing numbers of patients suffering from gastrointestinal disorders who are at primary risk for depression. These patients often have no awareness of their depression and therefore choose to see their gastroenterologists. Normally gastroenterologists advise the patients to undergo gastroscopy to investigate their possible digestive disorders while overlooking their depression. This study investigated the prevalence of the comorbidities between depression, depression-anxiety and organic diseases of upper gastrointestinal tract (UGI) among patients receiving gastroscopy in a large general hospital in China.MethodsA total of 707 patients who agreed to recommendation for gastroscopy were investigated using the nine-item Patient Health Questionnaire (PHQ-9). The patients of PHQ-9 scores ≥10 were further interviewed using the Hamilton depressive scale (HAMD), Hamilton anxiety scale (HAMA) and DSM-IV to confirm the diagnosis.ResultsAltogether, 412 patients were found to suffer from organic diseases of UGI based on the gastroscopy results. Of these, 51 patients and 34 were diagnosed with major depression and depression-anxiety respectively. The detection rate of depression by gastroenterologists was 3.92% while no depression-anxiety was diagnosed. Multiple logistic regression showed the course of disease, number of gastroscopies and age were significantly associated with major depression while educational level, income, age, and number of gastroscopies were significantly associated with depression-anxiety.ConclusionThe comorbidities rates between depression, depression-anxiety and organic diseases of UGI are higher than the general population in China. However, the detection rates of the comorbidities by gastroenterologists are low.